Post-activation performance enhancement (PAPE) increases jumping power in elite female volleyball athletes - Heynen, R.; Gross, M.; Betschen, T.; Hübner, K. (Sports, 2024)
This study investigated PAPE effects of two conditioning activities (CA) and recovery times on the peak jumping power (PP) of elite female volleyball athletes. Players performed CA separately: three sets of three repetitions of back squats with 85% of 1RM (BS) or one set of five depth drops (DD). PP was measured with countermovement (CMJ) and squat jumps (SJ) before (pre-test) and two minutes (post-test 1) and six hours (post-test 2) after each CA. BS significantly reduced PP at post-test 1 (CMJ and SJ: p < 0.04, d between -0.36 and -0.28). At post-test 2, following BS, PP for both jump forms was significantly greater than at post-test 1 (p < 0.001, d between 0.54 and 0.55) and at pre-test (p < 0.048, d between 0.21 and 0.30). DD increased PP significantly (CMJ and SJ p < 0.05, d between 0.40 and 0.41) relative to pre-test at post-test 2 (there was no significant difference between pre-test and post-test 1). Comparing BS with DD, there were no significant differences (p > 0.05). The greatest PAPE effects were observed six hours after BS. CA are recommended for female athletes to improve jumping performance, but individual responses should be determined prior to use.